The Effectiveness of Use of Electronic Signatures in Managing Banking Transactions Based on ITE Law - Rolib Sitorus; Cathryn Aurora Chiudy (LEGAL BRIEF, 2022)
The development of information technology that is used to assist human needs for the realization of an easier life has caused various changes, including the transition to electronic signatures. This study will present how the implementation of electronic signatures in banking transactions and the effectiveness in the use of electronic signatures for banking transactions based on the ITE Law. The government in regulating electronic signatures through legal policies and supervision of various legal institutions so that the focus in this paper is carried out with empirical normative juridical research methods by examining legal events in society. This study examines primary data and then secondary data consisting of primary, secondary and tertiary legal materials. The data collection method in this study was carried out through books, articles, and community behavior related to the problems studied. The type of research approach used is a qualitative research approach through the description, collection and interpretation of primary and secondary data. The data collected during the research will be analyzed using descriptive analysis techniques to get answers to the problems studied. The results of the research are expected to show that the use of electronic signatures in banking transactions is a collaboration between the Electronic Certification Operator (PSrE) and the bank itself. The effectiveness of the use of electronic signatures for banking transactions based on the ITE Law has fulfilled the elements as referred to in Article 11 and Article 12 paragraph 2 of the ITE Law related to the secure and safe use of electronic signatures by PSRE. The effectiveness of the use of electronic signatures for banking transactions can also be reviewed based on PP No. 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, as seen in Articles 60 to 64 that banking transactions in their implementation have used certified signatures. Based on Article 41 of POJK No. 77 of 2016 contains that the loan agreement can use an electronic signature. In this case, the author is of the opinion that electronic signatures in banking transactions are in line with applicable legal regulations and are effective in their use.